Analysis of finishing actions in men`s and women`s professional padel - Escudero-Tena, A.; Almonacid, B.; Martínez, J.; Martínez-Gallego, R.; Sánchez-Alcaraz, B. J.; Muñoz, B. (International Journal of Sports Science & Coaching, 2024)
The objective of this study was to analyse the effectiveness of finishing actions in men`s and women`s professional padel. To do this, the category, the type of finishing actions, the type of shot and the number of shots in 5513 points from five World Padel Tour tournaments were analysed. The results showed that men made more winners and fewer errors than women (p < 0.001); with smashes usually being the most frequently used shots to make winners, also highlighting the forehand off the wall smash in women's padel. The back wall shots and forehand or backhand shots without a wall appear as the most frequent errors in these finishing actions. Also, while men tend to make more errors with forehand volleys, women hit more winners with this shot. Men and women padel players make more errors (CSR = 6.7; CSR = 5.5) and fewer winners (CSR = -6.7; CSR = -5.5) in the first five shots of each point. However, they make fewer errors and more winning shots as the number of shots per point increases. These findings are highly relevant, since the style of play differs according to the gender of the players.